2014
DOI: 10.7785/tcrt.2012.500405
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Lymph Node Irradiation Including Pararectal Sentinel Nodes for Prostate Cancer Patients

Abstract: We aimed to assess the dosimetric impact of advanced delivery radiotherapy techniques using either intensity modulated x-ray beams (IMXT), volumetric modulated arc therapy (VMAT), or intensity modulated proton therapy (IMPT), for high-risk prostate cancer patients with sentinel nodes in the pararectal region. Twenty high-risk prostate cancer patients were included in a prospective trial evaluating sentinel nodes on pelvic SPECT acquisition. To be eligible for the dosimetric study, patients had to present with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…RapidArc (a form of volumetric modulated arc therapy (VMAT) implemented by Varian Medical Systems, Palo Alto, CA) and intensity modulated proton therapy (IMPT) are two most recent EBRT modalities that are used to treat prostate cancer. 1,2 One of the fundamental differences between these two techniques is that mega-voltage X-rays (photons) are used for RapidArc delivery, whereas protons are used for IMPT. Several researchers [2][3][4][5][6][7][8][9][10] have investigated the dosimetric impact of photon and proton therapy for the prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…RapidArc (a form of volumetric modulated arc therapy (VMAT) implemented by Varian Medical Systems, Palo Alto, CA) and intensity modulated proton therapy (IMPT) are two most recent EBRT modalities that are used to treat prostate cancer. 1,2 One of the fundamental differences between these two techniques is that mega-voltage X-rays (photons) are used for RapidArc delivery, whereas protons are used for IMPT. Several researchers [2][3][4][5][6][7][8][9][10] have investigated the dosimetric impact of photon and proton therapy for the prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 One of the fundamental differences between these two techniques is that mega-voltage X-rays (photons) are used for RapidArc delivery, whereas protons are used for IMPT. Several researchers [2][3][4][5][6][7][8][9][10] have investigated the dosimetric impact of photon and proton therapy for the prostate cancer. Earlier studies 4-10 using proton therapy were mostly focused on double scattering and uniform scanning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trying to irradiate all possible areas of lymphatic drainage in all patients may increase intestinal toxicity. Using IMRT, coverage of PR SLN is feasible without increasing the dose to the intestine [30]. Studies on a limited number of patients revealed the outcomes of SLN-based pelvic radiotherapy in prostate cancer [18,31].…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 The finite range of proton beams eliminates exit dose, 3 resulting in a reduction in integral dose of radiation and better sparing of organs at risk (OARs) in many cases. 4 , 5 , 6 , 7 , 8 , 9 However, the range of proton beams is subject to uncertainties that must be understood and accounted for in the treatment plan to avoid compromising clinical goals. 10 …”
Section: Introductionmentioning
confidence: 99%